G-Quadruplex DNA-binding quaternary alkaloids from Tylophora atrofolliculata. Issue 115 (7th December 2016) - Chen, Cheng-Yu; Bai, Li-Ping; Ke, Zhuo-Feng; Liu, Yan; Wang, Jing-Rong; Jiang, Zhi-Hong
Abstract : Quaternary alkaloids from T. atrofolliculata with human telomeric DNA G-quadruplex binding capacity. Abstract : Four new quaternary phenanthroindolizidine alkaloids (1–4 ) were isolated from the whole plants of Tylophora atrofolliculata . Their structures were elucidated on the basis of spectroscopic methods including 1D, 2D NMR and HRESIMS analyses. By utilizing electrospray ionization time-of-flight mass spectrometry (ESI-TOF-MS), all the compounds (1–8 ) were measured for G-quadruplex DNA-binding activities with human telomeric DNA d[(TTAGGG)4 TTA], since stabilization of quadruplexes in telomeric DNA by small molecules could result in telomere shortening and tumor suppression. Among all tested alkaloids, tylophoridicine D (7 ) exhibited the strongest capacity in binding to G-quadruplex DNA. Analyses of structure–activity relationship (SAR) revealed the critical factors associated with binding activity, i.e. quaternary ammonium cation and molecular planarity, substitution patterns at phenanthrene ring. This is the first report of the activity of quaternary phenanthroindolizidine alkaloids binding with human telomeric G-quadruplex DNA.